Residual life assessment of the historical road riveted bridges - Aleksandar Sedmak; Dorin Radu; Mihajlo Aranđelović; Simon Sedmak; Radu Băncilă (Engineering Fracture Mechanics, 2024)
Numerous roads and railways network steel bridges exist with more than 100 years in service, often of great historical value. The in-service safety assessment of these structures is a complex problem which requires interdisciplinary approaches – from civil engineering application of Eurocodes or European recommendation for fatigue life estimation, up to an in-depth assessment by means of fracture mechanics. This article emphasizes the importance of rehabilitating the structure of existing steel bridges, considering the historical monument character of these structures, as well as the reuse of existing structures. Toward this aim, the study case for a historical riveted steel bridge build in the beginning of the twentieth century is presented, with an assessment method considering the structural integrity by means of fracture mechanics. Based on this case study, the paper is proposing an algorithm to assess historical steel bridges. The results of in-depth XFEM analysis with different crack size in the area of a riveted joint are also presented, in order to validate the algorithm.
Keywords: Historical steel bridges; Structural integrity; Fracture mechanics